2011
DOI: 10.1002/jsfa.4309
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient composition of the marine snail (Hexaplex trunculus) from the Tunisian Mediterranean coasts

Abstract: This study suggests that H. trunculus is an important source of protein and essential amino acids. Furthermore, the snail lipidic fraction contains high proportions of polyunsaturated fatty acids benefical for human health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
34
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 34 publications
2
34
2
Order By: Relevance
“…Indeed, this station located in the Bizerte lagoon is characterized by low hydrodynamics leading to high accumulation of contaminants. The concentrations registered in the present analyses (35.4-179.0 μg/g dw) are lower than those reported in H. trunculus from Sfax (243-534 μg/g dw; Zarai et al 2011). The Cr contamination in the studied stations was weak and decreased throughout the sampling period.…”
Section: Discussioncontrasting
confidence: 83%
See 3 more Smart Citations
“…Indeed, this station located in the Bizerte lagoon is characterized by low hydrodynamics leading to high accumulation of contaminants. The concentrations registered in the present analyses (35.4-179.0 μg/g dw) are lower than those reported in H. trunculus from Sfax (243-534 μg/g dw; Zarai et al 2011). The Cr contamination in the studied stations was weak and decreased throughout the sampling period.…”
Section: Discussioncontrasting
confidence: 83%
“…In SF, the phosphoric acid factory started reducing its activity since many years, aiming to cease definitely the production in 2016, after being transferred to a non-coastal area in order to protect the marine environment around Sfax. Compared to analogous studies, the present levels of Cu in H. trunculus (31.9-363.1 μg/g dw) are higher than those reported for this species in the Bizerte lagoon (8-235, 41.6-241.1), France (33-134), and Spain (17.7-47.2) (Roméo et al 2006;Gharbi-Bouraoui et al 2008;Catsiki and Arnoux 1987;María-Cervantes et al 2009) but lower than those registered in Sfax (450.9 μg/g dw) and Italy (976 μg/g dw) (Lorenzini and Orlando 1994;Zarai et al 2011).…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…By comparison, studies on predatory gastropod whelks have generally found higher protein than that reported for herbivores, for example, the Muricidae Chicoreus ramosus 36% (Xavier Ramesh and Ayyakkannu ); Hexaplex trunculus 48% (Zarai et al. ); Rapana venosa 55.88 ± 2.04% (Celik et al. ) and as high as 80% in Thais haemastoma (Belisle and Stickle ).…”
Section: Discussionmentioning
confidence: 88%